The concerted amyloid-beta clearance of LRP1 and ABCB1/P-gp across the blood-brain barrier is linked by PICALM - Storck, Steffen; Hartz, Anika; Bernard, Jessica; Wolf, Andrea; Kachlmeier, André; Mahringer, Anne; Weggen, Sascha; Pahnke, Jens; Pietrzik, Claus U. (Brain, behavior and immunity, 2018)
The accumulation of neurotoxic amyloid-beta (Aβ) in the brain is a characteristic hallmark of Alzheimer’s disease (AD). The blood-brain barrier (BBB) provides a large surface area and has been shown to be an important mediator for removal of brain Aβ. Both, the ABC transporter P-glycoprotein (ABCB1/P-gp) and the receptor low-density lipoprotein receptor-related protein 1 (LRP1) have been implicated to play crucial roles in Aβ efflux from brain. Here, with immunoprecipitation experiments, co-immunostainings and dual inhibition of ABCB1/P-gp and LRP1, we show that both proteins are functionally linked, mediating a concerted transcytosis of Aβ through endothelial cells. Late-onset AD risk factor Phosphatidylinositol binding clathrin assembly protein (PICALM) is associated with both ABCB1/P-gp and LRP1 representing a functional link and guiding both proteins through the brain endothelium. Together, our results give more mechanistic insight on Aβ transport across the BBB and show that the functional interplay of different clearance proteins is needed for the rapid removal of Aβ from the brain.